DIAGNOSIS AND TREATMENT OF AXENFELD-RIEGER SYNDROME - Matylda Czerwonka; Katarzyna Kurza; Julianna Podolec; Silvia Ciraolo; Agnieszka Kulczycka-Rowicka; Joanna Wojda; Katarzyna Lesiczka-Fedoryj; Anna Walczak; Zuzanna Kościuszko; Adam Sobiński (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Axenfeld-Rieger syndrome (ARS) is a rare congenital disorder characterized by anterior segment dysgenesis and diverse systemic anomalies. Mutations in genes such as PITX2 and FOXC1 are most commonly implicated in its pathogenesis. The condition significantly affects vision, primarily due to structural disruption of the visual axis and the high incidence of secondary glaucoma. Aim of the study: The purpose of this study is to provide an updated overview of Axenfeld-Rieger syndrome, with emphasis on its historical background, genetic mechanisms, clinical manifestations, and current therapeutic strategies. Research materials and methods: A systematic review of scientific and medical literature was conducted using PubMed and Google Scholar databases. Conclusions: Genetic testing and comprehensive clinical evaluation are crucial for accurate diagnosis and optimal management of ARS. Due to its multisystem nature, care should be coordinated within a multidisciplinary framework. Early recognition of glaucoma and other systemic manifestations is essential to improve long-term outcomes.